2016
DOI: 10.1016/j.cjtee.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Operative management of a shear fracture of the bilateral capitellum: A case report and review of the literature

Abstract: Fracture of bilateral capitulum humeri is a very rare injury. We present a case of a 38-year-old woman, affected by a shear fracture of bilateral capitellum after a motorcycle accident. Intervention was carried out through a lateral approach on both sides and direct fixation of the fragment with headless screws. Consolidation was achieved and no signs of avascular necrosis occurred at 24 months of follow-up. The patient returned to her previous activities with no functional limitations. To the best of our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Also, no incidence of post-traumatic osteoarthritis of the elbow joint and avascular necrosis of the capitellum was reported in our case series, which is similar to several studies [6,[18][19]. In our view, if the soft tissues attached to the capitellum is preserved, proper reduction and stable fixation with less damage to the articular cartilage is done, the incidence of these complications is minimal.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Also, no incidence of post-traumatic osteoarthritis of the elbow joint and avascular necrosis of the capitellum was reported in our case series, which is similar to several studies [6,[18][19]. In our view, if the soft tissues attached to the capitellum is preserved, proper reduction and stable fixation with less damage to the articular cartilage is done, the incidence of these complications is minimal.…”
Section: Discussionsupporting
confidence: 90%
“…This injury pattern was associated with injuries of the lateral collateral ligament (LCL) and medial collateral ligament (MCL). So ligamentous stability must be assessed in these cases [2][3] [2,6]. In our study, no associated LCL or MCL injuries were found as checked in the operating room after anesthesia was given to the patient.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The average MEPI score was more than 90 for both groups, which corresponds to an excellent outcome. These results are consistent with several related studies, which showed that poor results were only obtained in capitellar fractures with posterior comminution [2, 810]. Based on our experience, the anterolateral approach can expose the capitellum and trochlea widely by directly approaching the anterior aspect of the elbow.…”
Section: Discussionsupporting
confidence: 92%